Some observations on the spermatogenesis in the testes of rabbit (Basrah Journal of Veterinary Research)
The seminiferous tubules of the testes of rabbits were lined by multilayered germ cells . The first layer was occupied by the spermatogonia , which were differentiated into type A(dusty type) spermatogonia, Intermediate type and type B (crusty type) spermatogonia. Pictures of Preleptotene, Leptotene, Zygotene ,Pachytene, Diplotene and Diakinesis. Primary spermatocytes were found and followed by secondary spermatocytes. Reading the morphological changes, the spermatid proposed 10 stages of cellular association during the cycle of the seminiferous epithelium in rabbit .